Simulation of nanosecond IR laser annealing of cerium gadolinium oxide. Issue 11 (September 2018) - Mariño, Mariana; Breuil, Philippe; Rieu, Mathilde; Jamon, Damien; Rampnoux, Jean-Michel; Viricelle, Jean-Paul; Garrelie, Florence
Abstract: Laser induced densification of ceramic oxide has shown great promises. However to control this process in regards of the final properties of the material, it is necessary to understand phenomena occurring during laser matter interaction, especially heat diffusion through the material. A thermal simulation of cerium gadolinium oxide (CGO) submitted to infrared laser pulses is presented. In order to determine the temperature profile during laser treatment, optical properties of CGO must be known; for this purpose, ellipsometry measurements were performed in order to obtain absorption coefficient and reflectivity. Finally, a thermal model based on heat equation was developed. Experimental observations of irradiated CGO surfaces were in agreement with the simulation results, in particular at maximum temperature when the material reaches fusion.